Brief acoustic approach of nasal consonants of nomatsigenga with special attention to the velar nasal /ŋ - Talancha de la Cruz, Jorge Martín (2022)
This study presents a brief acoustic approach to the nasal consonants of the Nomatsigenga language with special emphasis on the velar nasal. The analysis aims to document the acoustic properties of the nasals in Nomatsigenga and, at the same time, to show that there are features of this class of sounds -especially the velar nasal- in the language that have been little investigated. One of these features is the presence of an antiformant, which is located from two spectral plots: narrow band FFT (Fast Fourier Transform) and cepstrum. From this finding, it could be concluded that the first antiformant for the nomatsigenga nasal phonemes is located approximately around 830 Hz in the labial nasal /m/, between 1500 Hz and 1800 Hz in the alveolar nasal /n/ and, in the case of the velar nasal /ŋ/, it could be determined that the first antiformant is located approximately at the frequency of 3670 Hz in females and 3470 Hz in males. Finally, the range of the palatalized alveolar nasal allophone [nj] is approximately 3300 to 3600 Hz.